2016
DOI: 10.18632/oncotarget.8066
|View full text |Cite
|
Sign up to set email alerts
|

Small ubiquitin-related modifier 1 is involved in hepatocellular carcinoma progression via mediating p65 nuclear translocation

Abstract: Small ubiquitin-related modifier (SUMO) proteins participate in a post-translational modification called SUMOylation and regulate a variety of intracellular processes, such as targeting proteins for nuclear import. The nuclear transport of p65 results in the activation of NF-κB, and p65 contains several SUMO interacting motifs (SIMs). However, the relationship between p65 and SUMO1 in hepatocellular carcinoma (HCC) remains unclear. In this study, we demonstrated the potential roles of SUMO1 in HCC via the regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…Our previous data showed that SUMO1 overexpression up‐regulated the nuclear transport of p65, and SUMO1 knockdown down‐regulated p65 nuclear translocation in hepatoma cells . However, our data also showed that SUMO1, either by overexpression or knockdown, led to inhibition of the NF‐κB transcriptional activity . The underlying mechanism is unclear.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Our previous data showed that SUMO1 overexpression up‐regulated the nuclear transport of p65, and SUMO1 knockdown down‐regulated p65 nuclear translocation in hepatoma cells . However, our data also showed that SUMO1, either by overexpression or knockdown, led to inhibition of the NF‐κB transcriptional activity . The underlying mechanism is unclear.…”
Section: Discussionmentioning
confidence: 51%
“…The underlying mechanism is unclear. p65, as a transcriptional factor, can be SUMOylated by SUMO1 and SUMO2/3 proteins in hepatoma cells . Interestingly, we found that SUMO1 knockdown inhibited the interaction of MANF and p65 in the nucleus.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In details, p65 SUMOylation could be mediated by SUMO proteins that recruit an inhibitor of p65 in nucleus may be via SUMO-2/3 that has been described to inhibit nuclear import of p65 (58). Subsequentially, SUMO-2 or SUMO-3 induced the cytoplasmic level of p65 and may suppress its transcriptional activity (57,59). …”
Section: P65mentioning
confidence: 99%